Infectious syphilis in Canada: 2003-2012 - Totten, S (Can Commun Dis Rep, 2015)
BACKGROUND: In the 1990s, rates of reported cases of infectious syphilis were relatively low and were similar among males and females. In 2001, rates began to increase, particularly among males. OBJECTIVE: To identify trends in reported cases of infectious syphilis in Canada from January 1, 2003 to December 31, 2012. METHODS: Notifiable disease reports were submitted to the Public Health Agency of Canada by provincial and territorial epidemiological units and data were summarized by age and sex. RESULTS: Rates of reported cases of infectious syphilis increased by 101.0% between 2003 and 2012, from 2.9 to 5.8 per 100,000. Over this time frame, rates increased among males by 128.3% and decreased among females by 40.9%. In males, rates of infectious syphilis were highest among those aged 25 to 29; in females, rates were highest among those aged 20 to 24. CONCLUSION: In Canada, as in many countries, rates of reported infectious syphilis cases in males have markedly increased over the last 10 years.